What is six sigma? - Pande, Peter S. (McGraw-Hill, 2002)
Six Sigma is today's most talked-about system for improving the quality of organizational processes. Written by bestselling author Peter Pande, What Is Six Sigma? is a concise summary of the core themes and processes of Six Sigma. Unlike almost all other books on Six Sigma, it is written for the employees of organizations rolling out Six Sigma ƯƯnot just managers. This helpful overview describes what Six Sigma is, why companies are implementing it, and how employees can make it a success in their own organizations. Based on the bestselling The Six Sigma Way, this accessable introduction to Six Sigma answers typical employee questions, concerns, and even skepticism about this revolutionary program.